Literature Review: Faktor-Faktor Yang Berhubungan Dengan Kejadian Diare Pada Balita - Andinatania, Marcella; Utama, Winda Trijayanthi Utama; Daulay, Suryani Agustina Daulay; Sutarto (Medula, 2024)
Diarrhea is a condition characterized by frequent loose or watery stools, typically occurring more than three times per day. Diarrhea can lead to decreased appetite, abdominal pain, fatigue, and weight loss. Inadequate management of diarrhea can result in dehydration, which may eventually lead to death. Diarrhea in toddlers is one of the main causes of morbidity and death in children throughout the world, especially in developing countries4. According to data from the World Health Organization (WHO), diarrhea causes approximately 525,000 deaths among children under five years old each year, equating to nearly 1,400 deaths per day. The prevalence of diarrhea in Indonesia is 6.4% in infants under one year, 7.4% in children aged 1-4 years, and 4.3% across all age groups. This study aims to provide information on the factors associated with the incidence of diarrhea in children under five, based on a review of the literature. The research method employed is a literature review, using online databases such as Google Scholar to search for scholarly journals and articles. This literature review includes 10 journals published between 2020 and 2024. The results of this study reveal several factors associated with the occurrence of diarrhea in young children, including personal hygiene and handwashing habits, maternal knowledge, information exposure, socioeconomic status, child age, exclusive breastfeeding, immunization, diet, water quality, and environmental sanitation.